Returns to foreign education: yet another but different cross country analysis - Max Gruetter (Institute for the Study of Labor (IZA), 2005)
The main interest of this paper is to compare the value of education systems of different countries. For this reason I use data on workers who have completed their education before immigrating to Switzerland to estimate a country specific return to education. I estimate the standard Mincer-equation with the extension that I additionally allow for country specific returns to education. Results show that there are important differences between the returns to different education systems within Switzerland in the value of the basic education on the one hand and the return to an additional year of education on the other hand.
Keywords: C13; J61; I21; 330; return to education; immigration; international; Bildungswesen; Vergleich; International; Einwanderung; Bildungsniveau; Vergleich; Schweiz